IMPLEMENTASI MANAJEMEN ASESMEN NASIONAL BERBASIS KOMPUTER ( ANBK) DI SDN 236/IX AUR DURI II TAHUN 2025 - Janati, Salsabila; Firman; Hansein Arif Wijaya (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the implementation of the Computer-Based National Assessment (ANBK) at SDN 236/IX Aur Duri II using the POAC management approach. This study uses a qualitative approach with a descriptive method. Data collection techniques were carried out through interviews, observation, and documentation. The informants in this study included the principal, proctor, technician, ANBK supervisors, and ANBK participants. The results of the study indicate that in the planning aspect, the school has prepared the ANBK planning in accordance with central guidelines. In the organizing aspect, the division of tasks of the ANBK committee has been carried out clearly in accordance with their respective roles and responsibilities. In the actuating aspect, ANBK was implemented through the stages of simulation, rehearsal, and main implementation, although technical obstacles were still encountered. In the controlling aspect, supervision was carried out by external supervisors during the implementation as well as administrative and system supervision; however, evaluation and follow-up have not yet been carried out. Based on the results of the study, it can be concluded that the implementation of ANBK at SDN 236/IX Aur Duri II has been carried out fairly well in accordance with the POAC management functions, although improvements are still needed in technical support, more anticipatory planning, and the strengthening of supervision and continuous evaluation.